Asymmetric synthesis of evoninic acid. (11th May 2022) - Nagai, Toshiya; Wang, Yinghua; Hagiwara, Koichi; Inoue, Masayuki
Graphical abstract: Abstract: Evoninic acid (3 ) is a component of a 14-membered bislactone of bioactive dihydro-β-agarofuran sesquiterpenoids. The unique structure of 3 is characterized by C2′, C3′-disubstituted pyridine and vicinal C7′ S, C8′ S -dimethyl groups. Here we report a new synthetic route to enantiopure 3 . A chiral oxazolidinone controlled the stereochemical outcome of olefin hydrogenation, establishing the absolute configuration of the C7′ S -methyl group. The C7′ S -stereocenter then influenced the diastereoselectivity to install the C8′ S -methyl group.